Accuracy of molecular biology techniques for the diagnosis of Strongyloides stercoralis infection-A systematic review and meta-analysis. - Dora Buonfrate; Ana Requena-Mendez; Andrea Angheben; Michela Cinquini; Mario Cruciani; Andrea Fittipaldo; Giovanni Giorli; Federico Gobbi; Chiara Piubelli; Zeno Bisoffi (Public Library of Science (PLoS), 2018)
Strongyloides stercoralis infection is a neglected tropical disease which can lead to severe symptoms and even death in immunosuppressed people. Unfortunately, its diagnosis is hampered by the lack of a gold standard, as the sensitivity of traditional parasitological tests (including microscopic examination of stool samples and coproculture) is low. Hence, alternative diagnostic methods, such as molecular biology techniques (mostly polymerase chain reaction, PCR) have been implemented. However, there are discrepancies in the reported accuracy of PCR.A systematic review with meta-analysis was conducted in order to evaluate the accuracy of PCR for the diagnosis of S. stercoralis infection. The protocol was registered with PROSPERO International Prospective Register of Systematic Reviews (record: CRD42016054298). Fourteen studies, 12 of which evaluating real-time PCR, were included in the analysis. The specificity of the techniques resulted high (ranging from 93 to 95%, according to the reference test(s) used). When all molecular techniques were compared to parasitological methods, the sensitivity of PCR was assessed at 71.8% (95% CI 52.2-85.5), that decreased to 61.8% (95% CI 42.0-78.4) when serology was added among the reference tests. Similarly, sensitivity of real-time PCR resulted 64.4% (95% CI 46.2-77.7) when compared to parasitological methods only, 56.5% (95% CI 39.2-72.4) including serology.PCR might not be suitable for screening purpose, whereas it might have a role as a confirmatory test.